The value of reproduction: multiple livelihoods, cultural labor, and immigrants in Iowa and North Carolina. Issue 1 (2nd January 2020) - Griffith, David
ABSTRACT: In the US South and Midwest, early immigrant populations consisted primarily of young, Latinos recruited to work in low-wage jobs. After six or seven years, family members from Mexico and Central America began joining early arrivals, changing the character of immigrant interactions with host residents and institutions. While many natives viewed the single men as migrant workers, important for economic services, the arrival of women and children stimulated ambivalent reactions in North Carolina and Iowa rural communities. This suggests that native perceptions of immigrants can be traced, in part, to immigrants' roles in local economies, including their participation in multiple livelihoods and their deployment of cultural labor. The contradiction between anti-immigrant sentiments and the need for immigrant labour can be understood as a reaction to increasingly precarious economic conditions facing both natives and immigrants in the twenty-first century and the changing values of productive and reproductive economies.